5(2x-4)-(3x+1)=2

Simple and best practice solution for 5(2x-4)-(3x+1)=2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(2x-4)-(3x+1)=2 equation:


Simplifying
5(2x + -4) + -1(3x + 1) = 2

Reorder the terms:
5(-4 + 2x) + -1(3x + 1) = 2
(-4 * 5 + 2x * 5) + -1(3x + 1) = 2
(-20 + 10x) + -1(3x + 1) = 2

Reorder the terms:
-20 + 10x + -1(1 + 3x) = 2
-20 + 10x + (1 * -1 + 3x * -1) = 2
-20 + 10x + (-1 + -3x) = 2

Reorder the terms:
-20 + -1 + 10x + -3x = 2

Combine like terms: -20 + -1 = -21
-21 + 10x + -3x = 2

Combine like terms: 10x + -3x = 7x
-21 + 7x = 2

Solving
-21 + 7x = 2

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '21' to each side of the equation.
-21 + 21 + 7x = 2 + 21

Combine like terms: -21 + 21 = 0
0 + 7x = 2 + 21
7x = 2 + 21

Combine like terms: 2 + 21 = 23
7x = 23

Divide each side by '7'.
x = 3.285714286

Simplifying
x = 3.285714286

See similar equations:

| 9+1/9h=9 | | -6=x/3+4 | | 4x+6+8=3 | | 8(2.4r-3.1s)-6(10-4.3s)= | | x^2+4xy-4y^2-9=0 | | 5+22a=2+10/22 | | 1/4c+2=8 | | 8/4=(6)(0) | | -.2(x+10)-.25(x-4)=x+8 | | 6(X+2)-7=18 | | 0.7t=0.3+0.4t | | 4x-2=9x+1 | | -9x+12+4(3x-3)=7(x-2)-14 | | -6=x/3 | | -11.2+4(2.1+q)=8 | | -5(5x+5)-4+8x= | | -6(-3a-4)= | | -17r=17 | | -5+11x=11x-5 | | -8/3b=5/1 | | 25-x/8=12.5 | | 1/3x+7=14 | | 6y/7-3/8y | | m+5m-5=7 | | 2x+7x-4=95 | | 900/16 | | 6(2x-4)=4 | | (1/3)(x-3)=4-(2x+3) | | 5(1-4x)+x= | | 4+2/5x=4/15x | | 0.45x+0.05(4-x)=0.10(34) | | (128x^8y^12)^(1/6) |

Equations solver categories